Effectiveness of Research Based Booklet Media of Conventional Biotechnology Application As A Supplement Of Biotechnology Teaching Materials in Senior High School - Rani, Bone Kartika; Widiyaningrum, Priyantini; Anggraito, Yustinus Ulung (Universitas Negeri Semarang, 2020)
The implementation of learning using booklet media of conventional biotechnology application on biotechnology materials is expected to be able to help the students achieve of all basic competencies of learning and can improve student learning outcomes which are still low. The booklet was developed based on the results of the study, and then validated by experts to test the feasibility of the booklet. This study aims to analyse the effectiveness of the conventional biotechnology application booklet media. This study uses a pre-experimental design with one-group pretest-posttest design. The trial was conducted on the students of class XII MIPA 1 and XII MIPA 2 in NU 1 Kradenan High School in the 2019/2020 school year taken by purposive sampling technique. The results showed that the application of conventional biotechnology booklets was effectively used as a supplement for teaching biotechnology materials in high school. The average of N-gain 0,71 indicates that there was an increase in learning outcomes from pre-test to post-test with high criteria. The average classical completeness reached 92%, the average percentage of student attitudes reached 80% and the average student skills reached 81% with effective criteria. Based on the results of the study, the use of booklets is recommended in learning biotechnology to improve student learning outcomes in the cognitive, affective and psychomotor domains.